Adolescents' social support networks and long-term psychosocial outcomes. (December 2022) - Seok, Deborah; Doom, Jenalee R.
The current study examined how adolescents' social support networks are associated with long-term psychosocial outcomes (depressive symptoms and romantic relationship quality) in a nationally representative sample of adolescents followed into adulthood. Data were from 14, 800 participants who completed in-home interviews during Wave I (grades 7–12) and Wave IV (24–32 years) of the National Longitudinal Study of Adolescent to Adult Health. Using latent class analysis, we identified three profiles of adolescent social support across parents, friends, teachers, and adults: (1) high support from all sources, (2) low teacher support and high support from other sources, and (3) low teacher/adult and moderate parent/friend support. The third profile reported significantly higher increases in depressive symptoms from adolescence to young adulthood and lower romantic relationship quality in young adulthood than the other two profiles, but the "low teacher/high other support" group did not significantly differ from the "high support from everyone" group. Furthermore, multiple regression analyses indicated that adult and teacher support each interacted with parent support to predict outcomes during adulthood. These results highlight the advantage of having multiple supports in one's social network and emphasize the importance of understanding how adolescents' overall profile of relationships promotes their well-being in young adulthood.